Correlation between agronomic and environmental phoshorus analyses of selected soils - Nthejane, 'Mabatho Margaret (University of the Free State, 2012)
In crop production phosphorus (P) is an essential nutrient for crop growth, and hence P fertilization is necessary to achieve optimum yields. However, this can induces in soil a P concentration which may contributes to eutrophication of fresh water bodies. Soil P tests are therefore considered very useful in setting threshold values important for both agronomic and environmental management purposes. Soil P tests developed from a water pollution protection point unlike agronomic P tests are not easily adapted for use on a routine basis because they are not considered, for this purpose, and this could make agronomic P tests more practical for routine environmental P assessment also. Determination of appropriate agronomic P tests for this purpose however, involves evaluating the potential use of the tests for environmental purposes. Hence, the objective of this study was to review the current methods used to determine the agronomic and environmental P status of soils, and to establish whether P extracted from a range of soils by various agronomic and/or environmental P determination methods are related or not. Soil samples from the orthic A horison were collected in three cropping areas in the Free State province, namely Jacobsdal, Bloemfontein, and Ficksburg. These samples were treated with K2HPO4 to induce different phosphorus concentration levels and then incubated at room temperature for three months. During incubation the samples were subjected to several wetting and drying cycles to ensure that the applied phosphorus equilibrated. The samples were then analysed for P using the extractants of Olsen, Bray 1, Truog, ISFEI and citric acid commonly employed for routine analysis to establish the agronomic P status of soils. In order to establish the environmental P status of the soils, the samples were analysed for using the extractants calcium chloride (CaCl2) and ammonium oxalate [(NH4)2C2O4.H2O]. The latter was used to calculate the degree of phosphorus saturation (DPSox). The results showed significant relationships among agronomic P tests when data of individual soils were analysed separately (r2=0.65-0.99) and, when data of all soils from a sampling area were pooled (r2=0.52-0.87). All the relationships were significant for the Ficksburg soils (r2≥0.55) and for the Bloemfontein soils (r2≥0.82) but not for the Jacobsdal soils. For the latter soils the Truog-P correlations with Olsen-P (r2=0.44), Bray 1-P (r2=0.42) and ISFEI-P (r2=0.35) were not significant, probably due to that they are calcareous. Significant relationships were also obtained for P extracted by the environmental P tests when regression analysis was done for each individual soil (r2≥0.80). However, when data of soils from a sampling area were pooled significant relationships were obtained for Bloemfontein soils (r2=0.92) and Ficksburg soils (r2=0.56) while Jacbosdal soils (r2=0.33) showed an insignificant relationship. Pooling data of all soils from the three sampling areas also resulted with a lower correlation coefficient (r2=0.40) implying a poor relationship between the environmental P tests. The correlation between P extracted by the agronomic tests and CaCl2-P showed positive relationships (r2 ≥0.57) except in a few instances. Truog-P and citric acid-P showed a poor correlation with CaCl2-P when the Jacobsdal soils’ data were pooled (r2=0.22 and 0.35 respectively). Pooling of all soils’ data resulted also in a poor correlation between CaCl2-P and Truog –P (r2= 0.28). The DPSox correlated significantly with the extractable P of all agronomic tests when the individual soil’s data were analysed separately (r2 ≥0.73). However, when data of all soils from a sampling areas were pooled for regression analysis, all relationships were significant for the Bloemfontein soils (r2 ≥0.70), but not for the Jacobsdal soils, and Ficksburg soils. Pooling data of all soils from the three sites resulted with a positive relationship between DPSox and the extractable P of all agronomic tests (r2 ≥0.50), except ISFEI (r2 ≥0.45). The threshold values estimated for agronomic tests with regression equations from CaCl2-P DPSox threshold values varied greatly between individual soils and even the soils groups of a sampling area. The threshold values for all soils when based on CaCl2 implied that if the extractable P status of cropped soils are maintained at optimum levels for Bray 1, Truog, ISFEI and citric acid the soils may be a threat to water pollution. The opposite is true with the estimated threshold values when based on DPSox. The results therefore showed that agronomic tests can be used also for environmental management of P although only the Olsen test showed the potential for developing a single threshold value for all soils.

In gewasproduksie is fosfor (P) ‘n essensiële voedingstof vir gewasgroei en daarom is P bemesting nodig om optimum opbrengste te kry. Nietemin, dit kan in grond ‘n P konsentrasie induseer wat mag bydrae tot die eutrofikasie van varswaterliggame. Grond P toetse word daarom as nuttig beskou om drumpelwaardes vir agronomiese en omgewingsbestuur daar te stel. Grond P toetse wat ontwikkel is met die oog daarop om waterbesoedeling te verhoed word nie oorwag om soos agronomiese P toetse op ‘n roetine basis gebruik te word nie, en dit maak agronomiese P toetse moontlik geskik vir roetine omgewing P assessering ook. Dus was die doel met die studie om ‘n oorsig te kry van die huidige metodes wat gebruik word om die agronomiese en omgewing P status van gronde te bepaal, en vas te stel of die geëkstraheerde P deur die verskillende agronomiese en omgewing P bepalingsmetodes verwant is of nie. Grondmonsters van die ortiese A horison is in drie gewasverbouiingsgebiede in die Vrystaat provinsie ingesamel, naamlik Jacobsdal, Bloemfontein en Ficksburg. Hierdie monsters is met K2HPO4 behandel om fosforkonsentrasievlakke te induseer en daarna by kamertemperatuur vir drie maande geïnkubeer. Gedurende inkubasie is die monsters aan verskeie benatting- en uitdrogingsiklusse onderwerp om te verseker dat die toegediende fosfor ewewig bereik. Die monsters is daarna vir P ontleed deur die ekstraheermiddels van Olsen, Bray 1, Truog, ISFEI en sitroensuur te gebruik omdat hulle algemeen vir roetine ontledings aangewend word om die agronomiese P status van gronde vas te stel. Om die omgewing P status van die gronde vas te stel, is die ekstraheermiddels kalsiumchloried (CaCl2) en ammoniumoksalaat [(NH4)2C2O4.H2O] gebruik. Laasgenoemde is gebruik om die graad van fosforversading (DPSox) te berken. Die resultate het getoon dat daar tussen die agronomiese P toetse betekenisvolle verwantskappe is wanneer die data van die indiwiduele gronde ontleed is (r2 = 0.65-0.99), en wanneer die data van al die gronde van ‘n monsteringsgebied gepoel is (r2 = 0.52-0.87). Al die verwantskappe vir die Ficksburggronde (r2 ≥ 0.55) en vir die Bloemfonteingronde (r2 ≥ 0.82) was betekenisvol, maar nie vir die Jacobsdalgronde nie. Vir laasgenoemde gronde was die Truog-P korrelasies met Olsen-P (r2 = 0.44), Bray 1-P (r2 = 0.42) en ISFEI-P (r2 = 0.35) nie betekenisvol nie, moontlik omdat hulle kalkhoudend is. v Betekenisvolle interaksies is ook gekry vir geëkstraheerde P met omgewing P toetse wanneer regressie-ontledings vir elke indiwiduele grond gedoen is (r2 ≥ 0.80). Nietemin, wanneer data van gronde vanaf ‘n monteringsgebied gepoel is, is betekenisvolle verwantskappe vir Bloemfonteingronde (r2 = 0.92) en Ficksburggronde (r2 = 0.56) gekry terwyl Jacobsdalgronde (r2 = 0.33) nie ‘n betekenisvolle verwantskap getoon het. Poel van data van al die gronde van die drie monsteringsgebiede het ‘n laer korrelasiekoeffisiënt gegee (r2 = 0.40) wat ‘n swak verwantskap tussen die omgewing P toetse impliseer. Die korrelasie van geëkstraheerde P met die agronomiese toetse en CaCl2-P het behalwe vir enkele gevalle ‘n positiewe verwantskap (r2 ≥ 0.57) gegee. Truog-P en sitroensuur-P het ‘n swak korrelasie met CaCl2-P gegee wanneer die Jacobsdalgronde se data gepoel is (r2 = 0.22 en 0.35 onderskeidelik). Poel van al die gronde se data het tot ‘n swak korrelasie tussen CaCl2- P en Truog-P (r2 = 0.28) gelei. Die DPSox het betekenisvol met die ekstraheerbare P van al die agronomiese toetse gekorreleer wanneer die indiwiduele gronde se data afsonderlik ontleed is (r2 ≥ 0.73). Nietemin, wanneer die data van al die gronde van ‘n monsteringsgebied gepoel is vir regressie-ontleding, was al die verwantskappe vir die Bloemfonteingronde (r2 ≥ 0.70) betekenisvol, maar nie vir die Jacobsdalgronde en Ficksburggronde nie. Poel van die data van al die gronde vanaf die drie monsteringsgebiede het ‘n positiewe verwantskap tussen DPSox en die ekstrheerbare P van al die agronomiese toetse (r 2 ≥ 0.50) gegee, behalwe ISFEI (r2 ≥ 0.45). Die drumpelwaardes wat vir agronomiese toetse met regressievergelykings beraam is vanaf CaCl2-P en DPSox drumpelwaardes het baie tussen indiwiduele gronde en selfs grondgroepe van monsteringsgebiede gevarieer. Die drumpelwaardes vir al die gronde wanneer gebaseer op CaCl2 impliseer dat as die ekstraheerbare P status van verboude gronde by optimum vlakke vir Bray 1, Truog, ISFEI en sitroensuur gehou word die gronde ‘n bedreiging vir waterbesoedeling is. Die teenoorgestelde het gemanifesteer met die beraamde drumpelwaardes wanneer op DPSox gebaseer. Die resultate toon derhalwe dat agronomiese toetse ook gebruik kan word vir die omgewingsbestuur van P alhoewel slegs die Olsen toets die potensiaal getoon het vir die ontwikkeling van ‘n enkele drumpelwaarde vir al die gronde.
Dissertation (M.Sc.Agric. (Soil, Crop and Climate Sciences))--University of the Free State, 2012
Keywords: Threshold value; Water pollution; Crop production; Soil phosphorus test; Soils -- Phosphorus content; Crop science; Water -- Pollution; Agronomy